The Space of the Oral in the History of the construction of kingly territories in Gondar, Northern Ethiopia - Ramos, Manuel João (2012)
In the present paper I propose to bring together two literary traditions: that of European written documental sources on the history of Portuguese-Ethiopian contacts during the sixteenth-seventeenth centuries and oral literature recently collected in Northern Ethiopia concerning the political and religious transformations occurred in that same period in that region.